2024
DOI: 10.3390/electronics13040802
|View full text |Cite
|
Sign up to set email alerts
|

A Digital Twin Platform Integrating Process Parameter Simulation Solution for Intelligent Manufacturing

Haoran Wang,
Zuoqing Yang,
Quan Zhang
et al.

Abstract: The present work aims to develop a digital twin system typical of intelligent manufacturing applications, which has integrated visualization technologies, as well as the process parameter simulation solution. The application under consideration is a typical machining process, with a gantry machine tool controlled by Siemens Programmable Logic Controller(PLC) S7-1200. With the establishment of dual-directional data communication between the physical machine tool and its virtual counterpart based on TCP/IP proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…For the case study, a sorting station that has industrial sensors and actuators was used and the results showed that it is a generic and flexible architecture based on existing DT frameworks, and since they are open architectures for smart manufacturing, they are key to solving problems of interoperability. In [18], they developed a DT that has integrated visualization technologies and the simulation of process parameters. The implementation is carried out in a typical machining process, which has an S7-1200 PLC and bidirectional communication based on the TCP/IP protocol, with the simulation module based on finite element modeling (FEM), which was implemented in ANSYS, and the virtual model was developed in Unity.…”
Section: Related Workmentioning
confidence: 99%
“…For the case study, a sorting station that has industrial sensors and actuators was used and the results showed that it is a generic and flexible architecture based on existing DT frameworks, and since they are open architectures for smart manufacturing, they are key to solving problems of interoperability. In [18], they developed a DT that has integrated visualization technologies and the simulation of process parameters. The implementation is carried out in a typical machining process, which has an S7-1200 PLC and bidirectional communication based on the TCP/IP protocol, with the simulation module based on finite element modeling (FEM), which was implemented in ANSYS, and the virtual model was developed in Unity.…”
Section: Related Workmentioning
confidence: 99%